BROWN ADIPOSE TISSUE IN ADULTS: CONSENSUS POINTS AND GUIDELINES FOR FUTURE EXPERIMENTS - N. I. Volkova; M. I. Porksheyan; A. N. Gyulmagomedova (Медицинский вестник Юга России, 2016)
As part of a current worldwide effort to understand  the physiology of human BAT (hBAT) and whether its thermogenic activity can be manipulated to treat obesity, the workshop ‘‘Exploring the Roles of Brown Fat in Humans’’ was convened at the National Institutes of Health on February 25–26, 2014. Presentations and discussion indicated that hBAT and its physiological roles are complex, and research is needed to understand  the health impact of hBAT beyond thermogenesis and body weight regulation, and to define its interactions with core physiological processes like glucose homeostasis, cachexia, physical activity, bone structure, sleep, circadian rhythms. Consensus points and guidelines for future experiments have been summarized in the article of Aaron M. Cypess, Carol R. HaftMaren, R. Laughlin, Houchun H. Hu. Brown Fat in Humans: Consensus Points and Experimental Guidelines (Cell Metabolism. 2014 Sep 2;20(3):408-15. DOI: 10.1016/j.cmet.2014.07.025), which more extensive referat is presented by authors of this paper.